The Effect of Safety and Health Risks on Employee Productivity - Chairunnisa, Chairunnisa; Chaerudin, Chaerudin (Peneliti.net, 2025)
In a work environment that continues to develop, employee productivity has become the main focus for companies in achieving their business goals. However, it is often overlooked that factors such as safety and health risks have a significant impact on individual and organizational performance as a whole. The aim of this research is to determine the influence of safety and health risks on employee productivity. This research uses quantitative methods. Data collection techniques use questionnaires, observation, and literature study. The data collection techniques for this research are primary data obtained from questionnaires. The research population was 80 employees as well as the research sample. The research results of this Review Article are 1) Safety risks have no effect on employee productivity 2) Health has an effect on employee productivity